Pemikiran Ekonomi Kontemporer Tentang Nilai Nilai Ekonomi Islam - Moh Nafih (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2017)
This paper focusing on the view of Islamic economy from the perspective of contemporary thought, although contemporary thought insider researchers (Islam), but the islamic economist contemporary thought was apparent in analysis economic value in detail and didn’t based on with subyektifitas thinker own.With backed by some not being authentic in scientific Islam.This paper trying to peel Islamic economic contemporary thought with approach figures, where this study begins with outlines conception Islamic economy as a starter development value of economic analysis Islamic contemporary, then this paper trying to decipher views minds value of economic analysis Islamic contemporary.